Role of religious and cultural values in human capital - Gad, Salah; Shilova, Vera; Arutyunyan, Margarita; Sarsenov, Maxut (Opción, 2020)
The study aims to investigate the role of religious and cultural values in human capital. The research is based on the sociological research method. As a result, the actual and perceived cohesion of the neighbors’ matter. The actual cohesion seems to be more important for the youth to participate in extracurricular activities. In conclusion, the quality of the family, strong friendly relationship in the neighborhood and the increase in the social level of families with schoolchildren form the hidden potential for the rapid development of human capital